2018 IEEE Conference on Multimedia Information Processing and Retrieval (MIPR) 2018
DOI: 10.1109/mipr.2018.00015
|View full text |Cite
|
Sign up to set email alerts
|

Do They All Look the Same? Deciphering Chinese, Japanese and Koreans by Fine-Grained Deep Learning

Abstract: We study to what extend Chinese, Japanese and Korean faces can be classified and which facial attributes offer the most important cues. First, we propose a novel way of obtaining large numbers of facial images with nationality labels. Then we train state-of-the-art neural networks with these labeled images. We are able to achieve an accuracy of 75.03% in the classification task, with chances being 33.33% and human accuracy 38.89% . Further, we train multiple facial attribute classifiers to identify the most di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…Deep convolutional neural networks (CNN), on the other hand, have proven extremely powerful in image classification, usually reaching or surpassing human performance [29,11,36]. There exist quite a few studies that analyze selfies and other images posted on the social network [4,42].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Deep convolutional neural networks (CNN), on the other hand, have proven extremely powerful in image classification, usually reaching or surpassing human performance [29,11,36]. There exist quite a few studies that analyze selfies and other images posted on the social network [4,42].…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the recent success of deep convolutional neural networks (CNN), profile pictures and selfies have emerged as an integral data source for understanding individuals' demographics, sentiments and habits [4,42,36]. In particular, several studies of the 2016 presidential election have demonstrated the efficacy of using images for modeling political events.…”
Section: Profile Picturesmentioning
confidence: 99%
“…This idea leads us to mention the concept "soft biometrics", the analysis of body geometry, marks and tattoos that, unlike primary biometric traits, can be obtained at a distance without cooperation [7]. Several researchers [8][9][10][11] studied up to what point it is possible to infer and model race in face recognition. "How implicit, non-declarative racial category can be conceptually modelled and quantitatively inferred from the face?"…”
Section: Controversial Features Of Image and Voice Processingmentioning
confidence: 99%
“…Understanding the underlying features can help endow a variety of artificial-intelligence applications with humanlike performance. While face detection itself has been extensively studied in computer vision (Viola & Jones, 2001; Barnouti, Al-Dabbagh, & Matti, 2016; M. Wang & Deng, 2018), face categorization has largely been studied using only coarse distinctions such as ethnicity (Caucasian/Black/Asian; Brooks & Gwinn, 2010; Fu, He, & Hou, 2014) and gender (Tariq, Hu, & Huang, 2009; Fu, He & Hou, 2014; Y. Wang, Liao, Feng, Xu, & Luo, 2016). Even in humans, only coarse distinctions such as Caucasian/Black have been studied (Brooks & Gwinn, 2010; Fu, He & Hou, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the categories themselves can be made more fine-grained, thereby increasing task difficulty. While there has been some work on discriminating between finer grained geographical origin, such as with Chinese/Japanese/Korean (Y. Wang et al, 2016), Chinese subethnicities (Duan et al, 2010), and Myanmar (Tin & Sein, 2011), these studies have not systematically characterized human performance. In fact, it is an open question whether and how well humans can discriminate fine-grained face attributes across various world populations.…”
Section: Introductionmentioning
confidence: 99%